Attend to other water woes, too - Abd Razak, Dzulkifli (2005)
With the tsunami tragedy still fresh in our minds, perhaps many would be curious to know how much water there is on Earth. According to the National Geographic (Sept, 2002), if the Earth crust is smothered, the entire surface of the planet would be covered by 2682.24 metres of seawater. Put it another way, if all the seawater is evaporated, the Earth would be covered with more than 12.192 metres of salt. If so, it looks like there is enough water to go around, only that seawater is virtually not "usable". Ironically though, when it comes to "usable" water, the amount is no more that three per cent that of the seas and oceans.